From the Classroom to the Screen: The Power of Artistic Expression and Emotional Intelligence in Effective Online Teaching and Communication - Kadagidze, Lamara (European Scientific Journal, ESJ, 2024)
In the context of the increasing prevalence of online education, it is crucial to explore productive approaches that enhance student engagement and foster meaningful interactions. The article examines the role of emotional intelligence and artistic expression in online teaching and communication, drawing from original global survey research with over 200 teacher and educator respondents. The study emphasizes the effectiveness of artistic expression in capturing students’ attention, facilitating comprehension, and promoting creativity. The research explores strategies for incorporating emotional intelligence and artistic expression in online teaching, offering practical tips specifically suited for online English instruction. These strategies guide educators in creating dynamic online learning environments that optimize the learning experience and promote academic success. Acknowledging challenges, the paper sheds light on the hesitations and fears experienced by participants in being recorded or teaching in front of a camera. It highlights the need for training, resources, and guidelines to support educators in acquiring and developing artistic expression skills. By addressing challenges and integrating artistic expression, teachers can create impactful and supportive online learning environments that promote student engagement and provide an enriched learning experience in the digital era of education. Finally, the article provides valuable insights and practical recommendations to enhance online teaching practices.